ANALISIS KEPATUHAN WAJIB PAJAK ORANG PRIBADI BERDASARKAN GENDER, JENIS PEKERJAAN DAN TINGKAT PENDIDIKAN - Johan Putra Jaya Gea; Hari Purwanto; Nur Asih Triatmaja; Amy Wulandari (Universitas Boyolali, 2024)
This study aims to identify differences in the number of taxpayers at KPP Pratama Boyolali based on gender, type of work, and level of education. Data was collected through questionnaires which were distributed to one hundred people who answered. The Kruskal-Wallis method and independent t-test were used to test the hypotheses and analyze the data. The results of the study show that, although there is no difference between female and male taxpayers in the level of fulfillment of individual tax obligations, there is a difference between taxpayers who are employees and those who are not. In addition, this study found that there are differences in individual taxpayer compliance based on educational level, such as SMA-equivalent, Diploma 3, Bachelor, Diploma 4, Masters, or Doctoral.